Quantified,multi-scale X-ray fluorescence element mapping using the Maia detector array: Application to mineral deposit studies - Fisher, L.; Fougerouse, D.; Cleverley, J.; Ryan, C.; Micklethwaite, S.; Halfpenny, Angela; Hough, R.; Gee, M.; Paterson, D.; Howard, D.; Spiers, K. (Springer, 2014)
The Maia large solid-angle detector array and imaging system is capable of collecting high-resolution images of up to ~100 M pixels in size with dwell times of less than 0.2 ms per pixel and thus it is possible to document variation in textures associated with trace element chemistry by collecting quantified elemental maps of geological samples on the scale of entire thin sections in a short time frame (6–8 hr). The analysis is nondestructive and allows variation to be recognised on a centimetre scale while also recognising zonations at the micron scale.Studies of ore systems require microanalysis of samples to collect information on mineral chemistry in order to understand physiochemical conditions during ore genesis and alteration. Such studies contribute to the debate on whether precious metals are remobilised or introduced in multiple hydrothermal events. In this study we demonstrate the microanalytical capabilities of the Maia large solid-angle detector array and imaging system on the X-ray fluorescence microscopy beamline at the Australian Synchrotron to provide data for these studies. We present a series of case studies from orogenic gold deposits that illustrate the power of the Maia detector for constraining chemical zonations in sulphides and associated alteration minerals, which can be used to decipher ore-forming processes associated with gold deposition. A series of large-area (<7 cm2) elemental maps were collected with 2 to 4 μm pixel size using the Maia detector array. The data was processed using the GeoPIXE™ software package which allows variation in trace, minor and major element chemistry to be visualised in element maps. These maps are used to target further investigation with bulk spectra extracted and fitted for specific mineral grains and transects drawn through regions of interest. Analysis using the Maia detector offers a complementary method to map element distribution in geological samples that is both relatively fast and has a low detection limit for many elements of interest.